Overview of Motivation for Elderly Services for Control and Satisfaction in Polyclinic RSST Klaten - Azzaky; Amrizal Arief (Jurnal Endurance, 2019)
Background: Elderly during the examination were hoping to get good health care. Elderly will be motivated to check when he is satisfied with the services provided by health workers in hospitals. The purpose of this study was to Study the picture of the elderly to check the level of motivation and satisfaction in the service of RSST Klaten Policlinic. The design used in this study is Despriptif. The population is all the elderly who checked up in RSST Klaten. Samples are 96 respondents and taken with consecutive sampling technique. The variable in this study was to examine elderly motivation and service satisfaction. Data were collected with a structured interview, then processed based on the frequency distribution. Methods: The design of this study is descriptive. This study was conducted On September 1 - 30, 2019. Variable in this research is Elderly Motivation For Control and Service Satisfaction. In this research The population is all elderly ones Control at RSST Klaten Polyclinic Based on data from Medical Record Hospital SOERADJI TIRTONEGORO during the month August 2019 number of elderly patients who Control at RSST Klaten Polyclinic As many as 598 patients. Result The results of the study of 96 The respondent got none Respondents who have a level Less motivation, motivation level Quite as much as 2 respondents (2%) And high level of motivation as much 94 respondents (98%). Conclusions : Level of elderly motivation for Control at Polyclinic RSST Klaten majority is high As many as 94 respondents (98%). This matter Caused by age, type Sex and education of respondents and Satisfaction of the ministry Received patients at Polyclinic RSST Klaten.